2017
DOI: 10.1121/1.5014817
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic representation of 3D auditory space in the midbrain of the free-flying echolocating bat

Abstract: Essential to spatial orientation in the natural environment is a dynamic representation of direction and distance to objects. Despite the importance of 3D spatial localization to parse objects in the environment and to guide movement, most neurophysiological investigations of sensory mapping have been limited to studies of restrained subjects, tested with 2D, artificial stimuli. Here, we show for the first time that sensory neurons in the midbrain superior colliculus (SC) of the free-flying echolocating bat en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 102 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…therefore, had to be attentive to avoid collision between one another. To measure the bats' attention, we recorded their echolocation clicks (sonar signals), because many bat species have been shown to increase echolocation click rate when attention is needed; thus, echolocation provides an index of the bat's moment-to-moment attention [1][2][3][4][5][6][7][8][9] . Indeed, we found that, during cross-overs, the bats increased their echolocation click rate by around fourfold and click amplitude by around twofold (Fig.…”
Section: Articlementioning
confidence: 99%
See 3 more Smart Citations
“…therefore, had to be attentive to avoid collision between one another. To measure the bats' attention, we recorded their echolocation clicks (sonar signals), because many bat species have been shown to increase echolocation click rate when attention is needed; thus, echolocation provides an index of the bat's moment-to-moment attention [1][2][3][4][5][6][7][8][9] . Indeed, we found that, during cross-overs, the bats increased their echolocation click rate by around fourfold and click amplitude by around twofold (Fig.…”
Section: Articlementioning
confidence: 99%
“…1d-f and Extended Data Fig. 2), which suggests that they are attending to the other bat at these distances [1][2][3][4][5][6][7][8][9][38][39][40][41] ; to enable the analysis of an extra baseline, we considered a larger and symmetrical distance window of ±40 m, which enabled us to detect neuronal modulations and their return to baseline activity. Cross-overs that occurred less than 8 m from the landing balls were excluded from the analysis to avoid effects of landing and take-off (see the light grey vertical rectangles in Fig.…”
Section: Extracting Flights and Dividing Data To Different Behavioura...mentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of strong roll representation by head-motion and head-direction cells across species might relate to the fact that roll does not define the heading direction in threedimensional space, and thus might be less ethologically relevant for orienting behavior and navigation [16]. Notably, recent recordings in the superior colliculus of echolocating bats revealed neurons tuned to object position in egocentric threedimensional space [17]. The distance tuning of these neurons became shorter when bats actively inspected objects in the environment, suggesting that multidimensional neural representations in the superior colliculus could be modulated dynamically according to the behavioral needs of the animal.…”
mentioning
confidence: 99%